Результаты исследования нелинейных эффектов в микрополосковых линиях с ВТСП - Крикун, Е. В. (Weber, 2010)
In the paper the research of the current distribution along the superconductive microstrip vibrator is presented the current time dependencies in the different vibrator sections is defined.
Keywords: ВТСП; микрополосковые линии